2013
DOI: 10.3389/fncir.2013.00010
|View full text |Cite
|
Sign up to set email alerts
|

Chronic stress disrupts neural coherence between cortico-limbic structures

Abstract: Chronic stress impairs cognitive function, namely on tasks that rely on the integrity of cortico-limbic networks. To unravel the functional impact of progressive stress in cortico-limbic networks we measured neural activity and spectral coherences between the ventral hippocampus (vHIP) and the medial prefrontal cortex (mPFC) in rats subjected to short term stress (STS) and chronic unpredictable stress (CUS). CUS exposure consistently disrupted the spectral coherence between both areas for a wide range of frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 44 publications
(82 reference statements)
6
57
1
4
Order By: Relevance
“…This is indicative that the hyperactivation of vHPC and BLA was maintained over the course of the 3 weeks in stressed animals. Overactivation of vHPC and BLA by stress has been previously described in works on brain slices (Rainnie et al, 2004; Maggio and Segal, 2009) and anaesthetized rats (Kavushansky and Richter-Levin, 2006) including in the theta range (Oliveira et al, 2013) and appears to be in accordance with the dendritic hypertrophy observed in neurons of these brain regions after chronic stress exposure (Mitra et al, 2005), as a result of persistent hypercortisolism. Persistent hyperactivation of the amygdala with concurrent loss of inhibitory drive of the dHPC and the mPFC is also tied with the maladaptation of chronic stress through the contribution to the persistent overactivation of the HPA axis (Flandreau et al, 2012).…”
Section: Discussionsupporting
confidence: 66%
“…This is indicative that the hyperactivation of vHPC and BLA was maintained over the course of the 3 weeks in stressed animals. Overactivation of vHPC and BLA by stress has been previously described in works on brain slices (Rainnie et al, 2004; Maggio and Segal, 2009) and anaesthetized rats (Kavushansky and Richter-Levin, 2006) including in the theta range (Oliveira et al, 2013) and appears to be in accordance with the dendritic hypertrophy observed in neurons of these brain regions after chronic stress exposure (Mitra et al, 2005), as a result of persistent hypercortisolism. Persistent hyperactivation of the amygdala with concurrent loss of inhibitory drive of the dHPC and the mPFC is also tied with the maladaptation of chronic stress through the contribution to the persistent overactivation of the HPA axis (Flandreau et al, 2012).…”
Section: Discussionsupporting
confidence: 66%
“…4) in MGPNS rats, relative to controls. These findings are in sharp contrast with a study of brain signals recorded under anesthesia from rats chronically stressed during adulthood (Oliveira et al, 2013). These authors report increased power spectrum density (4-40 Hz range) in the vHPC and mPFC, but decreased coherence between these structures.…”
Section: Discussioncontrasting
confidence: 59%
“…Indeed, in rodent models of stress (Jacinto et al, 2013; Oliveira et al, 2013) and schizophrenia (Sigurdsson et al, 2010) coherences between VH and PFC are decreased. Likewise, the majority of studies in children with ASD have demonstrated reduced coherences (Coben et al, 2008; Khan et al, 2013).…”
Section: Discussionmentioning
confidence: 99%